Mechanical properties and consolidation of WC-8wt.%Ni hard materials by HFIHS and PCAS - Jeong, In Kyoon; Kim, Hwan Cheol; Doh, Jung Mann; Yoon, Jin Kook; Ko, In Yong; Shon, In Jin (ADVANCES IN NANOMATERIALS AND PROCESSING, PTS 1 AND 2, 2007)
Two methods, High-Frequency Induct ion-Heated Sintering (HFIHS) and Pulsed Current Activated Sintering (PCAS), were utilized to consolidate WC-8wt.%Ni hard materials. The demonstrated advantages of these processes are rapid densification to near theoretical density in a relatively short time and with insignificant change in grain size. The hardness, fracture toughness, and the relative density of the dense WC-8Ni composites produced by HFIHS and PCAS were investigated. And the effect of variation in particle size of WC powder on the sintering behavior and mechanical properties were investigated.